1997
DOI: 10.1159/000246103
|View full text |Cite
|
Sign up to set email alerts
|

Serum S100 – A Marker for Disease Monitoring in Metastatic Melanoma

Abstract: Background: S100 proteins are low-molecular-weight calcium-binding proteins and appear to play an important role in various cellular processes such as cell division and differentiation. In histopathology, S100 is widely accepted as the marker of choice for immunohistochemical identification of malignant melanoma. When S100 was detected in the serum of patients with malignant melanoma, it was suggested that serum S100 may be a useful marker for the stage of disease. Objective: The aim of this study was to exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
86
2
7

Year Published

1998
1998
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(99 citation statements)
references
References 0 publications
4
86
2
7
Order By: Relevance
“…Despite other data supporting the value of serum S-100B as a clinical marker for monitoring therapy response of metastatic melanoma during systemic therapies a clear drawback of this tumormarker is the fact that it has a false negative rate in one third of patients with metastases (7,28,29). In the present study 36% patients failed to show elevated S-100B values despite the presence of proven distant metastases.…”
Section: Discussioncontrasting
confidence: 75%
“…Despite other data supporting the value of serum S-100B as a clinical marker for monitoring therapy response of metastatic melanoma during systemic therapies a clear drawback of this tumormarker is the fact that it has a false negative rate in one third of patients with metastases (7,28,29). In the present study 36% patients failed to show elevated S-100B values despite the presence of proven distant metastases.…”
Section: Discussioncontrasting
confidence: 75%
“…Previous studies with the more insensitive immunoradiometric assay (IRMA) using pretreatment serum samples of patients with cutaneous malignant melanoma reported a relation between stage of the disease and the median concentration of S-1OOB protein, although an adequate assessment of the sensitivity of the S-1OOB was not possible (Von Schoultz et al, 1996;Henze et al, 1997). Bei Guo et al (1995) found positive S-1OOB values in 13% of stage IIIB patients, contrary to 33% in this study.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were confirmed by several early studies, which reported that the serum level of S100B correlated with clinical stage in patients with malignant melanoma, with the highest levels being seen in disseminated disease. [21][22][23][24][25] In 1995, a study of 126 patients by Guo et al 21 found that serum S100B concentrations were normal in all healthy patients and in those with benign skin lesions and elevated in 1.3%, 8.7%, and 73.9% of patients with stage I/II, III, and IV disease, respectively. Given the low incidence of elevated levels of S100B in serum in early-stage disease, S100B was not found to be useful for screening or early detection.…”
Section: Lactate Dehydrogenasementioning
confidence: 99%